Murine Models of Inflammatory Bowel Disease (IBD): Challenges of Modeling Human Disease. (January 2014) - DeVoss, Jason; Diehl, Lauri
Animal models of human disease are a critical tool in both basic research and drug development. The results of preclinical efficacy studies often inform progression of therapeutic candidates through the drug development pipeline; however, the extent to which results in inflammatory bowel disease (IBD) models predict human drug response is an ongoing concern. This review discusses how murine models are currently being used in IBD research. We focus on the considerations and caveats for commonly used models in preclinical efficacy studies and discuss the value of models that utilize specific pathogenic pathways of interest rather than model all aspects of human disease.